Hematological Factors and MRI in Covid-19 Infected may Predict the Prevalence of Multiple Sclerosis in the Post-Covid era - Bakhtiar Ebrahimirad; Mahnaz Taherianfard; Arash Mosarezaii (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: This study aimed to compare blood factors and MRI in MS+ participants (with a history of MS) and MS-(without a history of MS) to determine the prevalence of MS in MS- and increase the severity of the disease in MS+. Materials and Methods In this cross-sectional observational study, 80 human samples were selected from 20-50-year-olds infected with COVID-19 based on PCR tests at the time of infection from February 11th, 2020 to November 20th, 2021. The research method was explained to the participants and all of them filled out and signed the informed consent form CBC, ESR, ANA, and CRP were measured in the participants' blood samples. Then, an MRI scan was done on all participants to diagnose MS. Results: In age groups 31-40 and 41-50, ANA was significantly higher in MS+ than MS- participants. ANA was meaningfully higher in inpatient and outpatient MS+ than in inpatient and outpatient MS-. In MS+ men, CRP was higher than in MS- men. The MRI scan showed that MS plaques were observed in 13 patients with no history of MS before contracting COVID-19. Conclusion: The results showed that CRP and ANA were higher than healthy in all participants 2.5 years after the infection of COVID-19, but this increase was greater in hospitalized and MS+ participants. Also, the MRI showed MS plaques after contracting Covid-19.